Mezinárodní perspektivy politických regionů (Czech Journal of International Relations, 1996)
Bořek Hnízdo: International Perspectives on Political Regions. Institute for Central European Culture and Politics, Prague 1995, 121 pages, ISBN 80-85244-1-95-1.